ESTRUTURA DE COMUNIDADE DOS PEIXES ASSOCIADOS A PRADOS DE FANERÓGAMAS MARINHAS DA ILHA DO MARANHÃO - BRITO, Pâmella Silva de (2014)
The marine phanerogams meadows are important because they are nursery areas for many species of fish. In order to describe the community structure, temporal and spatial patterns of fish using Spartina alterniflora meadows of Maranhão Island present in tide macro region were held six samples of nine points in the period between July 2012 and June 2013, using a trawl net. A total of 11,660 individuals captured, representing 80 species, in which 13 are new record for the state of Maranhao. The sampled points are represented by a few abundant species (Rhinosardinia bahiensis, Atherinella brasiliensis, Lycengraulis grossidens, Lycengraulis batesii, incilis Mugil and Centegraulis edentulus) that demonstrated use the space according to interspecific preferences and presenting distribution patterns with the occurrence of distributed Juveniles throughout the year, suggesting that the studied environments are used by many species such as nursery areas and these have food preferences for zooplankton and mostly characterized as marine fish that frequent the estuary at some period of their life cycle. The species A. brasiliensis was constant in the spatial and temporal distribution, L. batesii was more abundant in the dry and the species L. grossidens, M. incilis, R. bahiensis, C. edentulus were dominant in the rainy season. The abiotic factors did not change much numerically, being only significant for dissolved oxygen between stations and different salinity for locations. We can see the meadows shown to be constant in the temporal variation and differed between sites, which showed no significant differences between the evaluation variables. Thus we can infer that the studied phytal environment is considered a nursery, it is frequented by several species of mostly juvenile fish that use this area as a place of recruitment, food and shelter; the dynamics of patches of seagrass were stable during the dry and rainy seasons and the composition and abundance of fish community is more explained by the spatial dynamics, but still have temporal distribution patterns, these features are typical of tropical environments that are inserted in mosaic adjacent environments.